Unveiling the Micronome of Cassava (Manihot esculenta Crantz) - Rogans, Sarah Jane (PLoS One, 2016)
MicroRNAs (miRNAs) are an important class of endogenous non-coding single-stranded small RNAs (21–24 nt in length), which serve as post-transcriptional negative regulators of gene expression in plants. Despite the economic importance of Manihot esculenta Crantz (cassava) only 153 putative cassava miRNAs (from multiple germplasm) are available to date in miRBase (Version 21), and identification of a number of miRNAs from the cassava EST database have been limited to comparisons with Arabidopsis. In this study, mature sequences of all known plant miRNAs were used as a query for homologous searches against cassava EST and GSS databases, and additional identification of novel and conserved miRNAs were gleaned from next generation sequencing (NGS) of two cassava landraces (T200 from southern Africa and TME3 from West Africa) at three different stages post explant transplantation and acclimatization. EST and GSS derived data revealed 259 and 32 miRNAs in cassava, and one of the miRNA families (miR2118) from previous studies has not been reported in cassava. NGS data collectively displayed expression of 289 conserved miRNAs in leaf tissue, of which 230 had not been reported previously. Of the 289 conserved miRNAs identified in T200 and TME3, 208 were isomiRs. Thirty-nine novel cassava-specific miRNAs of low abundance, belonging to 29 families, were identified. Thirty-eight (98.6%) of the putative new miRNAs identified by NGS have not been previously reported in cassava. Several miRNA targets were identified in T200 and TME3, highlighting differential temporal miRNA expression between the two cassava landraces. This study contributes to the expanding knowledge base of the micronome of this important crop.